ANTIRECESSIONARY ORGANIZATIONAL-ECONOMIC APPROACHES TO FUNDING OF DEVELOPMENT - V. Y. Ivanisov (Real Economics Publishing House, 2014)
The crisis of the developers of science intensive defense articles concerns with the loss of the companies’ scientific-manufacturing potential during the reforms of the domestic economics.  Restoration of the scientific-manufacturing potential of the developers of science intensive defense articles is complicated by some facts including that the state customer of the development employs organizational-economic approaches to the development funding that doesn’t correspond to the development features.  Organizational-economic approaches to the development funding used by the state customer create the prerequisites for their low profitability and unprofitableness, i.e. are “crisis”. Organizational-economic approaches to the development funding are realized through the contract management system of the development on the setting of the state contracts funding volume. It means that the contract management system of the development regarding funding (and price formation) and setting of manufacturing-property conditions doesn’t correspond to the development as a managed object. That inconsistency is one of the most important prerequisites of current crisis state of the science intensive products developers. Crisis state of the science intensive products developers shows up primarily in the decline of the quality and low profitability of the science intensive defense articles. The article shows antirecessionary organizational-economic approaches to funding and establishment of manufacturing-property conditions of the defense articles development that correspond to the development features, provide state support of the scientific-manufacturing potential of the developers of science intensive defense articles, provide antirecessionary development management and should be reflected in the contract management system of the development.